Edukasi Kebijakan Migas di Indonesia - Muhammad Ariyon; Fitrianti Fitrianti; Thoriqu Fathan (PELANTAR PRESS, 2023)
Oil and gas policy is important to know how the system is used in carrying out oil and gas industry activities in a country. Royalty Rate, Cost Recovery, Contractor Share, Domestic Market Obligation, Investment Credit, Signature Bonus, Production Bonus, First Tranche Petroleum and Corporate Tax Rate are things that will give effect in determining investment in this industry. Indonesia is a country in Southeast Asia that has relatively large reserves of oil and natural gas resources. The oil and gas industry has become the country's main income, to control this industrial activity a policy is needed. The target of community service activities are students of the Dumai Petroleum Vocational School, Dumai Municipality, Riau Province. The problem faced is that students and female students do not know much about and get information about Oil and Gas Management Policies in Indonesia. The solution offered by the team proposing community service is to provide material on knowledge of oil and gas management policies in Indonesia. The approach taken is in the form of observation, discussion, and question and answer with groups of partners, formulating problems and providing solutions to problems. The results achieved by this activity were that students at SMK Migas Dumai gained knowledge about Oil and Gas Management Policies in Indonesia. The expected output types are (1) scientific publications in journals/proceedings, (2) publications in mass media (print/electronic), and (3) increased knowledge